Vascular Remodeling and Immune Cell Infiltration in Splenic Artery Aneurysms. (July 2021) - Clément, Marc; Lareyre, Fabien; Loste, Alexia; Sannier, Aurélie; Burel-Vandenbos, Fanny; Massiot, Nicolas; Carboni, Joseph; Jean-Baptiste, Elixène; Caligiuri, Giuseppina; Nicoletti, Antonino; Raffort, Juliette
Rupture of splenic artery aneurysms (SAAs) is associated with a high mortality rate. The aim of this study was to identify the features of SAAs. Tissue sections from SAAs were compared to nonaneurysmal splenic arteries using various stains. The presence of intraluminal thrombus (ILT), vascular smooth muscle cells (VSMCs), cluster of differentiation (CD)-68+ phagocytes, myeloperoxidase+ neutrophils, CD3+, and CD20+ adaptive immune cells were studied using immunofluorescence microscopy. Analysis of SAAs revealed the presence of atherosclerotic lesions, calcifications, and ILT. Splenic artery aneurysms were characterized by a profound vascular remodeling with a dramatic loss of VSMCs, elastin degradation, adventitial fibrosis associated with enhanced apoptosis, and increased matrix metalloproteinase 9 expression. We observed an infiltration of immune cells comprising macrophages, neutrophils, T, and B cells. The T and B cells were found in the adventitial layer of SAAs, but their organization into tertiary lymphoid organs was halted. We failed to detect germinal centers even in the most organized T/B cell follicles and these lymphoid clusters lacked lymphoid stromal cells. This detailed histopathological characterization of the vascular remodeling during SAA showed that lymphoid neogenesis was incomplete, suggesting that critical mediators of their development must be missing.